2017
DOI: 10.5941/myco.2017.45.2.97
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Rhizosphere and Endosphere Fungi on the First-Class Endangered Plant Cypripedium japonicum

Abstract: Endangered native plant habitats and populations are rapidly disappearing because of climate and environmental changes. As a representative, the abundance of the first-class endangered wild plant, Cypripedium japonicum, has been rapidly decreasing in Korea. The purpose of this study was to evaluate the distribution of rhizosphere and endophytic fungi on C. japonicum in its native habitat. A total of 440 rhizosphere and 79 endosphere fungi isolates were isolated and identified on the basis of their molecular ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 12 publications
0
6
1
Order By: Relevance
“…Similar results were observed by Gottel et al about the Populus deltoides roots [20]; they found that variability was correlated with the rhizocompartment at a higher extent and different host plant at a lesser extent. In our study, we observed a lower diversity and evenness in the rhizospheric samples compared with the endosphere; on the contrary, Gottel et al's [20] and Gang et al's [21] studies found that the diversity of rhizosphere was higher than endosphere. In the rhizosphere, the diversity and evenness decreased with increasing forest ages, whereas in the endosphere, the diversity and evenness increased with increasing forest ages in our study.…”
Section: Discussioncontrasting
confidence: 90%
“…Similar results were observed by Gottel et al about the Populus deltoides roots [20]; they found that variability was correlated with the rhizocompartment at a higher extent and different host plant at a lesser extent. In our study, we observed a lower diversity and evenness in the rhizospheric samples compared with the endosphere; on the contrary, Gottel et al's [20] and Gang et al's [21] studies found that the diversity of rhizosphere was higher than endosphere. In the rhizosphere, the diversity and evenness decreased with increasing forest ages, whereas in the endosphere, the diversity and evenness increased with increasing forest ages in our study.…”
Section: Discussioncontrasting
confidence: 90%
“…For instance, the protection of rhizosphere bacteria Haliangium and Candidatus Koribacter synergistically protected Scutellaria tsinyunensis , an endangered species endemic to China ( Xu et al, 2021 ). Some rhizosphere microorganisms (e.g., Trichoderma , Mortierella , and Hypocrea ) were also assumed to protect the natural habitat of the first-class endangered plant Cypripedium japonicum and promote its reproduction ( Gang et al, 2017 ). Therefore, the investigation of rhizosphere bacterial communities can provide profound understandings for the survival and protection of rare and endangered species.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the protection of Rhizopogon yakushimensis synergistically protected Pinus amamiana , an endangered species endemic to Japan ( 25 ). Some fungi (e.g., Trichoderma , Mortierella , and Hypocrea ) were also assumed to protect the natural habitat of the first-class endangered plant Cypripedium japonicum and promote its reproduction ( 26 ). Therefore, the investigation of soil fungi is of great significance for understanding the growth and survival, resistance response, and protection of rare and endangered plants.…”
Section: Introductionmentioning
confidence: 99%